Genome-Wide Identification and Comparative Analysis of Copper Transporter Genes in Plants - ÖZYİĞİT, İBRAHİM İLKER (SPRINGER HEIDELBERG, 2017)
Copper (Cu) transporters have primary importance in maintenance of physiological limits of Cu home-ostasis in plants. However, structural characterization of Cu transporters in many plant species is still limited. In this study, a total of 78 potential Cu transporter genes were identified from 18 different plant species. Study revealed that Cu transporters could be characterized with a CTR protein family (PF04145) domain, three putative transmembrane domains (TMDs), a single exon number, and a basic character. Met-rich motifs at N-terminal region, MXXXM motif in TMD-2, and GXXXG motif in TMD-3 could be essential for Cu transport since they were highly conserved in all analyzed species. In phylogeny, a clear distinction was observed between Cu transporter sequences of lower and higher plants. General topological features of Cu transporters in higher plants-monocots and dicots-were highly conserved compared to lower plants. Identification of Cu transporter homologous in various plant species and their comparative analysis at gene and protein levels will become valuable theoretical basis for future studies aiming to further characterization and molecular manipulation of Cu transporters.
Keywords: Motif signature; Transmembrane domain (TMD); N-terminal; C-terminal; ARABIDOPSIS; HOMEOSTASIS; PREDICTION; MECHANISM; MEMBRANE; REVEALS; FAMILY; DOMAIN; YEAST; MOTIF